139 What happens to patients coded heart failure and discharged from the emergency department. (4th June 2021) - Oliver, Jan; Harris, Tom; McClure, Sam
Abstract : Heart failure is a common presentation to the emergency department, accounting for 5% of all medical admissions. Evidence from the national audit data base and our own local data confirms reduced mortality with specialist heart failure management. In our institution we recognized a group of patients that were seen in the emergency department and discharge without an admission and given a diagnosis of heart failure, these patients were not identified to our heart failure service. It is unclear if these patients have a formal diagnosis and what follow up is given. It is proposed that patients attending the emergency department and are considered fit for immediate discharge have sub optimal care. This study aims to evaluate the quality of care given to patients discharged from the emergency department where the primary diagnosis is heart failure by assessing three key performance indicators, NTproBNP, echocardiogram and follow up care. Methods: Attendances at the emergency department that were coded as having heart failure as a primary diagnosis during a six month period (01.10.18 - 31.03.19) were reviewed. The coded diagnosis included heart failure, left ventricular failure, acute pulmonary oedema or cardiomyopathy. This retrospective review of these attendances looked for three key performance indicators, NTproBNP assessment, echocardiogram and referral to heart failure/cardiology service as good quality care. Results: There were 227 attendances to the emergency department during the six months of the study period. 186 patients were admitted and 41 patients were discharged home. One patient visited the emergency department on 3 occasions therefore 39 patients attended the emergency department. The average age was 72.7 years with 59% male. A new diagnosis was established in 56% (22) with a pre existing diagnosis in the others. After the emergency department attendance 49% (19) had no follow up arranged. In 64% (25) no NTproBNP was undertaken. an echocardiogram was ordered for 28% (11). Patients not requiring an echocardiogram due to low NTproBNP or previous echo in last 6 months 30% (12). In 23% (9) none of the key indicators were undertaken; no NTproBNP, echocardiogram or follow up. Conclusion: Nearly a quarter of patients 23% (9) were discharge from the emergency department with a diagnosis of heart failure and did not receive any of the performance indicators of NTproBNP, echocardiogram or follow up. It is unsure if these patients do actually have heart failure and potentially may have been started on inappropriate medication or if they indeed do have heart failure and are not treated appropriately with the impact of increased mortality and further readmissions. This is a gap that has been identified in our local heart failure service provision and suspect that such a provision gap may be widespread in other areas. A redesign of our service is intended to address this gap. Conflict of Interest: None